MERAYAKAN KEHIDUPAN, MERAYAKAN KEBERAGAMAN: STUDI LITURGI DAN PENYAJIAN MUSIK KREATIF KONTEKSTUAL DALAM PERAYAAN HARI ULANG TAHUN REPUBLIK INDONESIA DI JEMAAT BETLEHEM OESAPA BARAT - Appris Yulianto Saefatu (Tambur : Journal of Music Creation, Study and Performance, 2021)
This paper aims to understand how to compose a liturgical form and a creative and contextual musical arrangement in church services. This study aims to produce a creative, contextual form of liturgical and musical accompaniment arrangements in church worship. The method used in this study is a qualitative description. This research is collaborative in nature by involving the congregation as a collaborator. In this study, the researcher took an action after the process of observing the reality of the liturgical form and accompanying music in the church environment, then the result of this study was that the researcher created a creative contextual form of liturgy and music in the celebration of the 73rd Indonesian Independence Day in the Bethlehem Congregation. Oesapa West